A CARE-compliant article: A case report and literature review of IgG4-related lung disease. Issue 47 (25th November 2022) - Ren, Hongmei; Han, Zhiqing; Zuo, Xiaoming; Wang, Jinping; Meng, Siming; Zheng, Cuixia
Abstract : Rationale: IgG4-related lung disease (IgG4-RLD) is an unusual disease, with various clinical manifestations and various chest imaging findings. The patients may have no respiratory symptoms. Therefore, diagnosis is challenging. This can easily cause misdiagnosis and mistreatment. Patient concerns: A 71-year-old male presented with chest pain, cough, and shortness of breath. Plain chest computed tomography scans showed multi-locus nodes at the center of the hilum. Diagnosis: Percutaneous lung biopsy was performed, and IgG4-RLD was diagnosed. Interventions: Prednisone was orally administered daily. Outcomes: The case's symptoms improved. The patient was discharged from the hospital. After 2 months of reexamination, his symptoms were relieved. Reexamination of the chest computed tomography showed that multi-locus nodes of the lung were obviously absorbed compared with those before. Lessons: IgG4-RLD is a rare respiratory disease. It has atypical clinical manifestations and chest images. We report the first case of IgG4-RLD showing multi-locus nodes centered on the hilar, hypertrophic mucosa; as well as a narrow and even occluded lumen.